Análise do ambiente institucional e organizacional da logística de exportações de grãos das cooperativas do Oeste do Paraná - Aguilar, Cristian Jair Paredes (2016)
The State of Parana is the second largest producer of grain commodities soybean and corn in Brazil. This scenario is related to strong and important presence of agricultural cooperativism in the western mesoregion. Thus, the cooperatives have major role in the modernization and advances in production, storage, marketing and processing of the productive chain products, which in addition to grains, include swine, chicken and dairy cattle. Given the importance of cooperatives in agribusiness in this mesoregion, this research aims at analyzing the influence of the institutional and organizational environment of logistics in the competitiveness of the grains of the western Parana cooperatives, using the theoretical approach of the institutional and organizational environment built by Farina et al. (1997). This master's thesis has exploratory and descriptive nature, using research of related literature, observation techniques and interviews with the agents involved in the different grain export routes. As a corollary, in the export route by the Port of Paranaga, the survey indicated that institutional failures in concessions generated major bottlenecks in road and rail transport to the port. The imbalance in the toll contracts, due to contractual changes, withdrawn the investments planned for the BR-277 road and increased toll rates for agribusiness. There are bottlenecks also in railroads due to institutional failures, referring to the lack of demand for works in the concession agreements, such as the adequation of the meter gauge and corrections in sinuous curves, which increase the transport time by the railway. As the waterway modal is the least used to transport grains in the region, the study also analyzed the potential driving force that the Parana-Paraguay Waterway (PPW) can bring to the competitiveness of the chain. Therefore, it was held the characterization of institutional and organizational elements involved in the operation of PPW by Paraguay. The results obtained in the grain export route by PPW showed that institutional constraints such as prohibition of transgenetics circulation in Parana, led the Paraguayan organizations to encourage the waterway alternative. Thus, the private sector investments in the waterway made Paraguay competitive in grain exports, with an outstanding waterway logistics infrastructure and trade integration with other Mercosur countries. Looking at the elements and opportunities present in the grains export route through Paranagua and the Paraguayan export route through PPW (Parana-Paraguay Waterway), it is possible to identify opportunities for Parana west mesoregion in the waterway modal. In Foz do Iguaçu there is al-ready a river terminal with access to the Parana-Paraguay Waterway and a shipping company, both created by the private sector in the region. If there is support for the development of PPW (Parana-Paraguay Waterway), whether by cooperatives and/or added to other western organizations and even from neighboring regions, the creation of a trade channel through the PPW may be an option for export (grains and other products) and importations that will extend the supply of logistics services for the region demands. Such alternative in logistics will increase competition with the road and rail modal available and currently used, generating competition in transport prices with the tendency to reduce logistics costs.